Episodic Memory and Learning Dysfunction Over an 18-Month Period in Preclinical and Prodromal Alzheimer's Disease. - Baker, Jenalle E; Lim, Yen Ying; Jaeger, Judith; Ames, David; Lautenschlager, Nicola T; Robertson, Joanne; Pietrzak, Robert H; Snyder, Peter J; Villemagne, Victor L; Rowe, Christopher C; Masters, Colin L; Maruff, Paul (J Alzheimers Dis, 2018)
Recent meta-analyses suggest that episodic memory impairment associated with preclinical Alzheimer's disease (AD) equates to 0.15-0.24 standard deviations below that of cognitively healthy older adults. The current study aimed to characterize impairments in verbal acquisition and recall detectable at a single assessment, and investigate how verbal learning and episodic memory deteriorates in preclinical AD. A verbal list-learning task, the International Shopping List Test (ISLT), was administered multiple times over an 18-month period, to three groups of participants: amyloid-beta negative healthy older adults (Aβ- CN; n = 50); Aβ+ positive healthy older adults (preclinical AD; n = 25); and Aβ+ positive individuals diagnosed with mild cognitive impairment (prodromal AD; n = 22). At baseline, there was no significant difference between the preclinical AD and control groups rate of acquisition, or total and delayed recall, however all indices were impaired in prodromal AD. Performance on ISLT total score improved in the control group over the 18-month period, but showed a moderate magnitude decline in the preclinical AD group (Cohen's d = - 0.63, [- 1.12, - 0.14]) and the prodromal AD group (Cohen's d = - 0.36, [- 0.94, 0.22]). No significant impairment in acquisition associated with preclinical AD was seen at baseline. Individuals with preclinical AD showed a significantly different performance on the ISLT total score over an 18-month period, compared to those without abnormal Aβ. Individuals with prodromal AD showed substantial impairment on the ISLT at baseline and declined to a greater extent over time.